GRAMMATICAL MISTAKES IN WRITING NARRATIVE TEXT BY EEC STUDENTS - Martina Andriani; Rusmi Saniti (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2020)
ABSTRACTThis article explores about grammatical mistakes in writing narrative text in English Extensive course (EEC). EEC is an English program held by Sanata Dharma University. In case, there are five  srtudents as participants that learn writing as subject in EEC. In learning writing, EEC students face some problems especially grammatical errrors. This article raises some problems and difficulties to write a narrative text by EEC students. This research used descriptive qualitative as a methodogy. Data collection are analyzed through the narrative text and the grammatical method. The aim of this research is to find, even in higher education level, there still found mistakes in grammar. Not mentioning vocabulary or certain spelling. Beside that reasearchers wants to find how much mistakes that has been made in grammar and mistakes that often made by students in learning writing. In conclusion, the result showed there was every student made error in each indicator. And the most error that students made was error in tense.Keywords: Grammatical Mistakes; Narrative Text; English Extension Course